2017
DOI: 10.1016/j.stemcr.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Elevated p53 Activities Restrict Differentiation Potential of MicroRNA-Deficient Pluripotent Stem Cells

Abstract: SummaryPluripotent stem cells (PSCs) deficient for microRNAs (miRNAs), such as Dgcr8−/− or Dicer−/– embryonic stem cells (ESCs), contain no mature miRNA and cannot differentiate into somatic cells. How miRNA deficiency causes differentiation defects remains poorly understood. Here, we report that miR-302 is sufficient to enable neural differentiation of differentiation-incompetent Dgcr8−/− ESCs. Our data showed that miR-302 directly suppresses the tumor suppressor p53, which is modestly upregulated in Dgcr8−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
9
0
1
Order By: Relevance
“…Teratoma formation assay was performed as described [20,27]. In brief, 2−5×10 6 iPSCs were suspended in 100 μl of DMEM/F12 medium containing 30% of human ESC-qualified Geltrex membrane matrix (Thermo Fisher) and injected subcutaneously into 4–6 week-old NOD scid gamma (NSG) mice (005557, Jackson Laboratory).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teratoma formation assay was performed as described [20,27]. In brief, 2−5×10 6 iPSCs were suspended in 100 μl of DMEM/F12 medium containing 30% of human ESC-qualified Geltrex membrane matrix (Thermo Fisher) and injected subcutaneously into 4–6 week-old NOD scid gamma (NSG) mice (005557, Jackson Laboratory).…”
Section: Methodsmentioning
confidence: 99%
“…All experiments involving lab animals were conducted in accordance with guidelines from the University of Alabama at Birmingham (UAB) and National Institute of Health. Teratoma formation assay was performed as described [20,27]. In brief, 2−5×10 6 iPSCs were suspended in 100 μl of DMEM/F12 medium containing 30% of human ESC-qualified Geltrex membrane matrix (Thermo Fisher) and injected subcutaneously into 4–6 week-old NOD scid gamma (NSG) mice (005557, Jackson Laboratory).…”
Section: Methodsmentioning
confidence: 99%
“…By suppressing both the CDK2 and CCND‐CDK4/6 cell cycle pathways, this cluster can regulate iPSC tumorigenicity during the G 1 ‐S phase transition . Moreover, some researchers have found that differentiation ability can be inhibited by elevated p53 activity in miRNA‐deficient iPSCs . Interestingly, miR‐302 can repress the expression of NR2F2 , a target gene verified by reporter luciferase assays and RT‐PCR, and stimulate the expression of OCT4 to promote cell pluripotency …”
Section: Regulatory Role and Mechanisms Of Mir‐302/367 Cluster Regardmentioning
confidence: 99%
“…34 In mouse iPSCs, p53 accumulation was shown to cause impaired neural differentiation, which was successfully overcome by p53 inactivation. 35 In summary, our findings suggest that augmented p53 signaling is the common process underlying HUWE1-promoted XLID syndromes. Our previous work showed that depending on the type of HUWE1 mutation, its stability and activity are differentially affected, which in turn can have specific impacts on p53 levels.…”
Section: Discussionmentioning
confidence: 64%